Drosophila epidermal cells are intrinsically mechanosensitive and modulate nociceptive behavioral outputs. - Yoshino, J.; Mali, S.S.; Williams, C.R.; Morita, T.; Emerson, C.E.; Arp, C.J.; Miller, S.E.; Yin, C.; Thé, L.; Hemmi, C.; Motoyoshi, M.; Ishii, K.; et al. (eLife, 2025)
Somatosensory neurons (SSNs) that detect and transduce mechanical, thermal, and chemical stimuli densely innervate an animal's skin. However, although epidermal cells provide the first point of contact for sensory stimuli, our understanding of roles that epidermal cells play in SSN function, particularly nociception, remains limited. Here, we show that stimulating Drosophila epidermal cells elicits activation of SSNs including nociceptors and triggers a variety of behavior outputs, including avoidance and escape. Further, we find that epidermal cells are intrinsically mechanosensitive and that epidermal mechanically evoked calcium responses require the store-operated calcium channel Orai. Epidermal cell stimulation augments larval responses to acute nociceptive stimuli and promotes prolonged hypersensitivity to subsequent mechanical stimuli. Hence, epidermal cells are key determinants of nociceptive sensitivity and sensitization, acting as primary sensors of noxious stimuli that tune nociceptor output and drive protective behaviors.